Escala de Centralidade do Acontecimento para Adolescentes - Matos, Marcela (2011)
The CES assesses the extent to which a memory for a stressful event (in this case a shame experience reported by each participant) forms a reference point for personal identity and to attribution of meaning to other experiences in a person's life. This self-report questionnaire consists of 20 items, rated on 5-point Likert scale (1-5), that measure three interdependent characteristics of a highly negative emotional event that load on to a single underlying factor: the extent to which the event is a central component of one's personal identity (e.g., "I feel that this event has become part of my identity."), is viewed as a landmark in one's life story (e.g., "I feel that this event has become a central part of my life story.") and acts as a reference point for inferences and attributions in everyday life (e.g., "This event has coloured the way I think and feel about other experiences.").